Energy and mass distributions of ions during depostition! of TiN by triode ion plating in BAI 730 M - Maček, Marijan (Kovine zlitine tehnologije, 1998)
On the basis of the results of the energy and mass spectroscopy, it was found that low voltage arc in combinataion with the arrangements of electrodes and coils to form the weak mirror magnetic vessel very efficiently ionize the gas and evaporate metal species in triode ion plating system BAI 730 M. Results show that the 95% of the Ti ion flux during the deposition of TiN consists of double charged ?$Ti^{++}$? ions accelerated toward the substrate with energiesfrom 90 to 120 eV. The rest (=5%) of Ti ions have energies from 45-60 eV (?$Ti^+$?) and about 0.1% even have energies over 135 eV.
Keywords: ionizacija; titan; plazma; spektroskopija